2004
DOI: 10.1080/02786820490426084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Structure and Hydration on the Uptake of Gas-Phase Sulfuric Acid by Charged Clusters/Ultrafine Particles

Abstract: The enhanced uptake of sulfuric acid molecules by charged clusters as a result of dipole-charge interaction is critical to the ionmediated nucleation of particles in the atmosphere. This article illustrates the effect of the structure of the gas-phase sulfuric acid and its hydrates on the uptake of the sulfuric acid molecules by the charged clusters/ultrafine particles. It is shown that the different structures of gas-phase sulfuric acid and its hydrates lead to very big (up to ∼230%) variations in the uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…On the other hand, this is not the most stable structure and its dipole moment is almost double that of the NAT-2 dipole moment value. Recently Nadykto et al [27,28] reported that the increment of the dipole moment of the molecular conformation will increase the value of the uptake coefficient of the cluster. This highlights the high reactivity of this molecular complex.…”
Section: Vibrational Frequencies and Ir Spectrum Analysismentioning
confidence: 98%
“…On the other hand, this is not the most stable structure and its dipole moment is almost double that of the NAT-2 dipole moment value. Recently Nadykto et al [27,28] reported that the increment of the dipole moment of the molecular conformation will increase the value of the uptake coefficient of the cluster. This highlights the high reactivity of this molecular complex.…”
Section: Vibrational Frequencies and Ir Spectrum Analysismentioning
confidence: 98%
“…Theoretical calculations predict that condensation of vapor molecules, especially of sulfuric acid and its hydrates, is faster for charged particles compared with neutral particles [ Yu and Turco , 2000; Laakso et al , 2003; Nadykto and Yu , 2003; Nadykto et al , 2004]. This means that charged nuclei are expected to grow faster in size than what neutral nuclei do.…”
Section: Applicability Of the Analytical Expressionsmentioning
confidence: 99%
“…Despite these uncertainties, the value of EF is expected to be close to unity for nuclei larger than about 3–5 nm in diameter, which means that the charging state is not significantly affected by this phenomenon in the size range that can be measured using current instrumentation. Below 3 nm, the value of EF increases rapidly with decreasing particle size and may reach values larger than 2 when the nuclei diameter approaches 1 nm [ Laakso et al , 2003; Nadykto and Yu , 2003; Nadykto et al , 2004].…”
Section: Applicability Of the Analytical Expressionsmentioning
confidence: 99%
“…Any plausible theory, however, must predict sufficiently high growth rates since freshly-nucleated clusters are scavenged away very rapidly by pre-existing particles (Kerminen et al, 2001). In particular, it has been suggested that the presence of electric charges in freshly-formed clusters enhance the uptake of polar molecules such as sulfuric acid, thereby giving a growth advantage to charged clusters over neutral ones (Yu and Turco, 2001;Nadykto and Yu, 2003;Nadykto et al, 2004). Atmospheric ions are thus expected to be involved in both nucleation and growth, but their overall importance to particle formation is an open question at present.…”
Section: Introductionmentioning
confidence: 99%